Lobbying and Compromise - Gil S. Epstein; Shmuel Nitzan (Center for Economic Studies and ifo Institute (CESifo), 2005)
The compromise enhancing effect of lobbying on public policy has been established in two typical settings. In the first, lobbies are assumed to act as 'principals' and the setters of the policy (the candidates in a Downsian electoral competition or the elected policy maker in a citizen- candidate model of electoral competition) are conceived as 'agents'. In the second setting, the proposed policies are solely determined by the lobbies who are assumed to take the dual role of 'principals' in one stage of the public-policy game and 'agents' in its second stage. The objective of this paper is to demonstrate that in the latter setting, the compromising effect of lobbying need not exist. Our reduced-form, two-stage public-policy contest, where two interest groups compete on the approval or rejection of the policy set by a politician, is sufficient to show that the proposed and possibly implemented policy can be more extreme and less efficient than the preferred policies of the interest groups. In such situations then more than the calf (interest groups) wish to suck the cow (politician) desires to suckle thereby threatening the public well being more than the lobbying interest groups. The main result specifies the conditions that give rise to such a situation under both the perfectly and imperfectly discriminating contests.
Keywords: D6; D72; 330; public-policy contests; interest groups; policy makers; lobbying; compromise; Interessenpolitik; Wettbewerb; Spieltheorie; Ökonomische Theorie der Demokratie; Agency Theory; Theorie